2015
DOI: 10.1039/c5nr04193g
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of the N impurity state in dilute GaNAs using scanning tunneling microscopy

Abstract: The interaction between nitrogen (N) impurity states in III-V compounds plays a key role in controlling optoelectronic properties of the host materials. Here, we use scanning tunneling microscopy to characterize the spatial distribution and electronic properties of N impurity states in dilute GaNAs. We demonstrated that the N impurity states can be directly visualized by taking empty state current images using the multipass scanning method. The N impurity states broadened over several nanometers and exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 34 publications
7
20
0
Order By: Relevance
“…[49,50] the peak position of the single nitrogen level in general shows up between +1.2 and +1.7 V. As illustrated well by the spectroscopy series of Ishida et al, the observed values in STS are dependent on the tip condition, hence, we are reluctant to compare the exact values resulting from STS. The difference observed with our value is most probably due to the use of illumination and a more intrinsic environment in our case.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…[49,50] the peak position of the single nitrogen level in general shows up between +1.2 and +1.7 V. As illustrated well by the spectroscopy series of Ishida et al, the observed values in STS are dependent on the tip condition, hence, we are reluctant to compare the exact values resulting from STS. The difference observed with our value is most probably due to the use of illumination and a more intrinsic environment in our case.…”
Section: Resultsmentioning
confidence: 78%
“…In previous X-STM measurements at room temperature [45][46][47][48] these features were not observed. A recent publication on X-STM measurements at 77 K reports a feature similar to B1 and B2, although the structure of the features was less clearly resolved [50]. Discussion of both B1 and B2 will be continued later.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations